MORPHOLOGY OF THE NEUROVASCULAR COMPONENTS IN PROSTHETIC BED TISSUE FORMATIONS - Yu. N. Mayboroda; M. V. Goman; E. V. Uryasyeva (Кубанский научный медицинский вестник)
By means of neurohistological and histochemical methods of investigation we traced the morphological changes in the neurovascular components and phosphatases of the hard and soft palate mucosa of denture-carriers and individuals who did not use removable dentures constructions in a comparative aspect. Certain individual differences in neural structures were revealed, as well as peculiarities of the degree of nerve structures destructive changes, the esterases content, their topography, the number and the ratio of neurovascular complexes. Morphological changes in the vascular system, apparently, are caused by a constant compression of the prosthetic bed tissue formations with dentures.